DYNAMICS OF MISCARRIAGE AMONG THE FEMALE POPULATION OF FERTILE AGE IN UKRAINE AND IN LVIV REGION IN 2014-2021 - Nataliia Timchenko; Taras Gutor (Acta Medica Leopoliensia)
Aim. The research aims at rationalizing of the epidemiological component in the process of developing a model for preventing miscarriage among the female population of Ukraine.